PENGARUH MODEL PEMBELAJARAN CRH BERBANTUAN MEDIA AUDIO VISUALTERHADAP HASIL BELAJAR IPS - Pratama, GH Andika (Journal for Lesson and Learning Studies, 2018)
This study aims to determine the difference of Fifth grade IPS learning outcomes of elementary school in Gugus II Tejakula Sub-district on even semester of 2017/2018 between group of students who are taught using Course Review Horay learning model with audio visual and group of students who are not taught using Course Review Horay learning model. This research is quasi experiment with non equivalent design post-test only control group design. The population of this study is all Fifth grade of elementary school students in Gugus II Tejakula sub-district academic year 2016/2017 in total of 162 students. The sample in this study is Fifth grade students of SD Negeri 5 Les in total 30 students and Fifth grade students of SD Negeri 1 Les counted 39 people, determined by random sampling technique. The result was obtained through multiple choice instrument test method which analyzed by using descriptive statistical and inferential statistical test (t-test). The result showed that there was a significant effect of IPS learning outcomes between groups of students who were taught using learning model of Course Reviews Horay helped by audio visual media and group of students who were not taught of using Course Review Horay model, with t-count = 2,384 bigger than t-tab = 1,980. This means that the difference application of learning model can affect the Fifth grade's IPS learning outcomes in Gugus II Tejakula sub-district even semester of academic year 2017/2018. Recommendation for the teachers in improving the Fifth grade's IPS learning outcomes in Sub-district II Tejakula is to use learning model of Course Review Horay assisted by audio visual media.